Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's solve each part step-by-step.
### Part (a): Find the inverse function [tex]\( f^{-1} \)[/tex]
Given the function [tex]\( f(x) = x^3 + 3 \)[/tex], we want to find its inverse [tex]\( f^{-1}(x) \)[/tex].
1. To find the inverse, we start by setting [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = x^3 + 3 \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ x = y^3 + 3 \][/tex]
3. Isolate [tex]\( y \)[/tex]:
[tex]\[ x - 3 = y^3 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = (x - 3)^{\frac{1}{3}} \][/tex]
So the inverse function is:
[tex]\[ f^{-1}(x) = (x - 3)^{\frac{1}{3}} \][/tex]
The inverse function is valid for all [tex]\( x \)[/tex] since the cubic root function is defined for all real numbers. Thus, the correct choice is:
[tex]\[ \boxed{D. \ f^{-1}(x) = (x-3)^{\frac{1}{3}}, \ \text{for all} \ x} \][/tex]
### Part (b): Verify the inverse function
We need to verify two things:
1. [tex]\( f(f^{-1}(x)) = x \)[/tex]
2. [tex]\( f^{-1}(f(x)) = x \)[/tex]
Let's verify both:
#### Verification 1: [tex]\( f(f^{-1}(x)) = x \)[/tex]
1. Start with [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(x) = (x - 3)^{\frac{1}{3}} \][/tex]
2. Substitute [tex]\( f^{-1}(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(f^{-1}(x)) = f((x - 3)^{\frac{1}{3}}) \][/tex]
3. Evaluate [tex]\( f \)[/tex]:
[tex]\[ f((x - 3)^{\frac{1}{3}}) = \left( (x - 3)^{\frac{1}{3}} \right)^3 + 3 \][/tex]
[tex]\[ = x - 3 + 3 \][/tex]
[tex]\[ = x \][/tex]
Thus, [tex]\( f(f^{-1}(x)) = x \)[/tex].
#### Verification 2: [tex]\( f^{-1}(f(x)) = x \)[/tex]
1. Start with [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = x^3 + 3 \][/tex]
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( f^{-1} \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}(x^3 + 3) \][/tex]
3. Evaluate [tex]\( f^{-1} \)[/tex]:
[tex]\[ f^{-1}(x^3 + 3) = \left( (x^3 + 3) - 3 \right)^{\frac{1}{3}} \][/tex]
[tex]\[ = (x^3)^{\frac{1}{3}} \][/tex]
[tex]\[ = x \][/tex]
Thus, [tex]\( f^{-1}(f(x)) = x \)[/tex].
### Conclusion on verification
Since both verifications are correct, we've shown that [tex]\( f(f^{-1}(x)) = x \)[/tex] and [tex]\( f^{-1}(f(x)) = x \)[/tex]. Therefore, our inverse function [tex]\( f^{-1}(x) = (x-3)^{\frac{1}{3}} \)[/tex] is indeed correct.
### Part (a): Find the inverse function [tex]\( f^{-1} \)[/tex]
Given the function [tex]\( f(x) = x^3 + 3 \)[/tex], we want to find its inverse [tex]\( f^{-1}(x) \)[/tex].
1. To find the inverse, we start by setting [tex]\( y = f(x) \)[/tex]:
[tex]\[ y = x^3 + 3 \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ x = y^3 + 3 \][/tex]
3. Isolate [tex]\( y \)[/tex]:
[tex]\[ x - 3 = y^3 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = (x - 3)^{\frac{1}{3}} \][/tex]
So the inverse function is:
[tex]\[ f^{-1}(x) = (x - 3)^{\frac{1}{3}} \][/tex]
The inverse function is valid for all [tex]\( x \)[/tex] since the cubic root function is defined for all real numbers. Thus, the correct choice is:
[tex]\[ \boxed{D. \ f^{-1}(x) = (x-3)^{\frac{1}{3}}, \ \text{for all} \ x} \][/tex]
### Part (b): Verify the inverse function
We need to verify two things:
1. [tex]\( f(f^{-1}(x)) = x \)[/tex]
2. [tex]\( f^{-1}(f(x)) = x \)[/tex]
Let's verify both:
#### Verification 1: [tex]\( f(f^{-1}(x)) = x \)[/tex]
1. Start with [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(x) = (x - 3)^{\frac{1}{3}} \][/tex]
2. Substitute [tex]\( f^{-1}(x) \)[/tex] into [tex]\( f \)[/tex]:
[tex]\[ f(f^{-1}(x)) = f((x - 3)^{\frac{1}{3}}) \][/tex]
3. Evaluate [tex]\( f \)[/tex]:
[tex]\[ f((x - 3)^{\frac{1}{3}}) = \left( (x - 3)^{\frac{1}{3}} \right)^3 + 3 \][/tex]
[tex]\[ = x - 3 + 3 \][/tex]
[tex]\[ = x \][/tex]
Thus, [tex]\( f(f^{-1}(x)) = x \)[/tex].
#### Verification 2: [tex]\( f^{-1}(f(x)) = x \)[/tex]
1. Start with [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = x^3 + 3 \][/tex]
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( f^{-1} \)[/tex]:
[tex]\[ f^{-1}(f(x)) = f^{-1}(x^3 + 3) \][/tex]
3. Evaluate [tex]\( f^{-1} \)[/tex]:
[tex]\[ f^{-1}(x^3 + 3) = \left( (x^3 + 3) - 3 \right)^{\frac{1}{3}} \][/tex]
[tex]\[ = (x^3)^{\frac{1}{3}} \][/tex]
[tex]\[ = x \][/tex]
Thus, [tex]\( f^{-1}(f(x)) = x \)[/tex].
### Conclusion on verification
Since both verifications are correct, we've shown that [tex]\( f(f^{-1}(x)) = x \)[/tex] and [tex]\( f^{-1}(f(x)) = x \)[/tex]. Therefore, our inverse function [tex]\( f^{-1}(x) = (x-3)^{\frac{1}{3}} \)[/tex] is indeed correct.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.